Young female athletes and knee extensor age-related profile - Rousanoglou, E.; Boudolos, K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Muscular strength can be likened to a skilled act (Kraemer and Newton, 2000) and is increased during developmental age (Van Praagh and Dore, 2002). Thus when higher mechanical loading occurs over a different knee angle range, such as in the track & field jumpers (TFJ) (Graham-Smith and Lees, 2005) and the volleyball players (VP) (Tokuyama et al., 2005), a sport and age-related profile may be exhibited in young athletes not only for maximal torque levels but also for the relations between the torque at the peak of the torque-angle curve and the torque at other knee angles (angle-angle (A-A) relationships). METHOD: Subjects were young (13-19yrs) female TFJ (n=20) and VP (n=21) devided into the youngest (more than 16.449yr) and the oldest age category (more than 16.500yr), similarly to the official competitive categories. The maximum knee extensor isometric torque (TMAX), developed ôas fast and hard as possibleö, was measured at 9 knee angles (10 grad increments randomized across subjects, from 10 to 90 grad, 2min rest). Statistics included (p<0.05), A) two way ANOVA (2 (Age or Group) X 9 (Angle)) for TMAX differences between the age categories or pair of groups, respectively, B) the Pearson's coefficient of correlation (r) squared (R2) and expressed as a percentage (%) for the A-A relationships and C) quadratic and linear curve fitting to the joint angle R2 trendlines, separately for each group and each age category. RESULTS & DISCUSSION: The same strength levels in both the youngest and the oldest TFJ (p>0.05), may be attributed to the demands for high muscular strength already from early training years (Kraemer and Newton, 2000), since they must overcome their whole body mass with just half of their lower extremities potential. The dominance of team tactical skills rather than strength in their training context, in combination with the developmental process (Van Praagh and Dore, 2002), possibly account for the significant greater TMAX in the oldest than the youngest VP (p<0.05). Almost all A-A relationships were significant at p=0.000 and, with the exception of the oldest VP, they were described by significant quadratic R2 joint angle trendlines, however, a greater R2 decrease was observed at the more extended or more flexed knee angles in the youngest than the oldest TFJ underlining the sport and age-related influence on the knee extensor A-A relationships. CONCLUSION: The age category as well as the sport-specific knee angle range should be accounted for when treating young athletic females 13-19yrs who are still in a developmental phase both technically and physically.